尺寸偏差作用下角接触球轴承载荷分布研究 - 周夕维; 徐华; 熊显智; 王琳 (Jixie chuandong)
The solution of load distribution of rolling element bearing is closely related to the calculation of some key performance indicators,such as load-carrying capacity,lubrication characteristics,fatigue life and so on.In view of dimension deviation of balls in manufacturing processing,a load distribution model of angular contact bearing in consideration of ball dimension deviation is put forward.Based on the load distribution model,the effects of dimension of off size,circumferential position,number and arrangement of ball dimension deviation on bearing load distribution and the effects of dimension deviation under different clearance are analyzed.Through calculation and analysis of 7218Bangular contact bearing,the follow conclusions are obtained.For single ball dimension deviation,it is found that the magnitude of ball contact loads fluctuation is linearly dependent on the value of dimension deviation,and has no correlation with bearing clearance.In addition,the variation of ball contact load is a function of circumferential position of dimension deviation.For multiple balls dimension deviation,both relative dimension deviation value and arrangement of balls dimension deviation have great effects on load distribution.